2021
DOI: 10.1101/2021.07.05.21260018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementation, adoption and perceptions of telemental health during the COVID-19 pandemic: a systematic review

Abstract: Background: Early in 2020, mental health services had to rapidly shift from face-to-face models of care to delivering the majority of treatments remotely (by video or phone call or occasionally messaging) due to the COVID-19 pandemic. This resulted in several challenges for staff and patients, but also in benefits such as convenience or increased access for people with impaired mobility or in rural areas. There is a need to understand the extent and impacts of telemental health implementation, and barriers and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 93 publications
(90 reference statements)
0
7
1
Order By: Relevance
“…Furthermore, in line with findings from Johnsson and Bulkeley and Li et al (2021), both clinicians and service-users identified challenges, even those who considered their experience to be positive, and their respective views were concordant overall. This pattern in findings across studies somewhat contradicts the conclusion from a recent review which concluded that telepsychiatry may not be suitable for certain individuals, including those with ASD (Appleton et al, 2021). Rather, present findings suggest that there may be some autistic individuals that benefit from remote delivery and others who do not, as indicated by the inter-YP variability perceived by both the YP themselves and clinicians.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, in line with findings from Johnsson and Bulkeley and Li et al (2021), both clinicians and service-users identified challenges, even those who considered their experience to be positive, and their respective views were concordant overall. This pattern in findings across studies somewhat contradicts the conclusion from a recent review which concluded that telepsychiatry may not be suitable for certain individuals, including those with ASD (Appleton et al, 2021). Rather, present findings suggest that there may be some autistic individuals that benefit from remote delivery and others who do not, as indicated by the inter-YP variability perceived by both the YP themselves and clinicians.…”
Section: Discussioncontrasting
confidence: 99%
“…Adoption of TMH has expanded during the COVID-19 pandemic to allow services to continue to offer mental health support despite social distancing restrictions. This shift in care delivery was often conducted rapidly as part of the emergency response to the pandemic, in which services had to adapt their existing face-to-face models of treatment to include remote forms of care (2). Some benefits to delivering mental health support in this way have been identified, for example, increasing access for service users who live remotely, have difficulty travelling, or find mental health care settings stigmatising or intimidating, and greater convenience for some service users (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also some challenges associated with this approach, for example, some service users may not have access to technology, internet connectivity, or a private space to use during TMH care, whilst others have identified challenges in developing and maintaining a therapeutic relationship (5,6). A recent systematic review also identified that TMH may not be suitable for all types of therapy, for example, exposure therapy or when treating trauma (2). This review also identified challenges in delivering TMH care to certain populations, for example, children and service users with learning difficulties or severe anxiety (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake of telemental health care increased rapidly during the COVID-19 pandemic as services moved from largely face-to-face models of care due to social distancing requirements (4,5). However, a systematic review conducted during the early stages of the pandemic identified a lack of evidence on the cost-effectiveness of telemental health interventions (4).…”
Section: Introductionmentioning
confidence: 99%